THE USE OF CREATIVE TASKS IN MEDICAL CHEMISTRY - Safarova, Nafisa Sulaymonovna (SCIENCE and SOCIETY, 2026)
The article examines methodological approaches designed to foster and enhance clinical thinking among medical students within the framework of the “Medical Chemistry” course. It highlights the significance of this discipline as a foundational element in educating future healthcare professionals and shaping their professional mindset. The study reviews and organizes active teaching methods aimed at integrating chemical knowledge with clinical application, promoting analytical competencies, improving the interpretation of laboratory findings, and supporting well-grounded professional decision-making. The findings indicate that the implementation of problem-based learning, case-based methods, interdisciplinary collaboration, and a contextual approach substantially improves the development of students’ clinical thinking skills.